Patient Satisfaction at Aisyiyah RSU Klaten - Siti Qomariyah; Istiatin; Sudarwati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Patient satisfaction in hospital services can also be achieved from the service system provided by the hospital. Hospitals as health service institutions are required to provide fast, quality and affordable services to provide satisfaction for patients. The purpose of this study is to determine the influence of waiting time, service quality, officer attitude and information technology on patient satisfaction at Aisyiyah Klaten Hospital. The method of this research is quantitative descriptive. The number of research respondents was 120, which was determined by accidental sampling technique. The results of the study showed that waiting time (p value 0.000), officer attitude (p value 0.008) and information technology (p value 0.015) had a positive and significant effect on patient satisfaction in health services at RSU 'Aisyiyah Klaten.The quality of service (p value 0.775) had no effect on patient satisfaction in health services at RSU 'Aisyiyah Klaten. The suggestion of this research is that information technology should be better and easily accessible so that patient satisfaction increases so that the quality of hospital services is even better. Keywords: satisfaction, service quality, officer attitude, information technology, waiting time